Anti-müllerian hormone and sertoli cell function in paediatric male hypogonadism - Grinspon, Romina (2010)
In the prepubertal male, Sertoli cells are the most active testicular cell population. Without stimulation tests, prepubertal hypogonadism can only be evidenced if Sertoli cell function is assessed. Anti-müllerian hormone (AMH) is a distinctive marker of the prepubertal Sertoli cell. Serum AMH is high from fetal life until puberty. In postnatal life, AMH testicular production is stimulated by FSH and potently inhibited by androgens. In anorchid patients, AMH is undetectable. In prepubertal males with fetal- or childhood-onset primary or central hypogonadism affecting the whole gonad, serum AMH is low. Conversely, when hypogonadism only affects Leydig cells (i.e., LH/human chorionic gonadotrophin receptor or steroidogenic enzyme defects), serum AMH is normal/high. AMH is also normal/high in patients with androgen insensitivity. In patients of pubertal age with central hypogonadism, AMH is low for Tanner stage - reflecting lack of FSH stimulus, - but high for age - reflecting lack of testosterone inhibitory effect. FSH treatment results in serum AMH rise, whereas human chorionic gonadotrophin treatment increases testosterone levels which inhibit AMH production. In conclusion, AMH determination is helpful in assessing gonadal function, without need for stimulation tests, and orientates the aetiological diagnosis of paediatric male hypogonadism. Furthermore, serum AMH is an excellent marker of FSH and androgen action in the testis.